Use of FRP in civil engineering systems - Cheah, Wenbin (2017)
The aim of this report is to explain and evaluate how Fibre Reinforced Polymers (FRPs) are being utilized in civil engineering systems. The use of FRPs in Civil Engineering Systems is growing. As FRPs are light-weight, resistant to corrosion and have high strength, civil engineers are beginning to shift their focus towards FRPs instead of conventional construction materials such as concrete and steel. FRPs are therefore widely utilized in reinforcing bars, seismic retrofitting of concrete columns, rehabilitation of deteriorating concrete structures and hybrid bridge decks.